Narrare più saggiamente: Un supplemento prosaico alla poetica dell’identità narrativa di Ricœur - Gregor, Brian (B@belonline, 2021)
This essay examines Ricœur’s account of narrative identity and asks the practical question of what it looks like to tell our stories – and narrate our selves – well. Ricœur sees good self-narration as freeing us from the grip of narcissism, and argues that literature offers models for telling our stories in a non-narcissistic way. I develop this insight by drawing on Gary Saul Morson’s theory of prosaics, which shows how literature can form better habits of self-narration by training us to attend to the small, contingent details of everyday life. I illustrate this point with Morson’s reading of Anna Karenina, Tolstoj’s masterpiece of prosaic fiction. This prosaic supplement to Ricœur’s account of narrative identity can show us what it might look like to narrate ourselves more wisely.